Physicochemical characterization of a new family of small alkyl phosphonium imide ionic liquids. (1st June 2016) - Hilder, M.; Girard, G.M.A.; Whitbread, K.; Zavorine, S.; Moser, M.; Nucciarone, D.; Forsyth, M.; MacFarlane, D.R.; Howlett, P.C.
Graphical abstract: Abstract: Despite their promising properties, phosphonium based ionic liquids have attracted little attention as compared to their nitrogen-based cation counterparts. This study focuses on the properties of a family of small phosphonium imide ionic liquids, as well as the effect of lithium salt addition to these. The 6 ionic liquids were either alkyl, cyclic or nitrile functionalised phoshonium cations with bis(trifluoromethanesulfonyl)imide, NTf2, or bis(fluorosulfonyl)imide (FSI) as anion. Amongst the properties investigated were ionic conductivity, viscosity, thermal behaviour, electrochemical stability and the reversibility of electrochemical lithium cycling. All ionic liquids showed very promising properties e.g. having low transition temperatures, high electrochemical stabilities, low viscosities and high conductivities. Particularly the trimethyl phosphonium ionic liquids showed some of the highest conductivities reported amongst phosphonium ionic liquids generally. The combination of electrochemical stability, high conductivity and reversible lithium cycling makes them promising systems for energy storage devices such as lithium batteries.